Analisis Dinamik Model Penyebaran Tumor Otak dengan Respon Sel Imun - Resti Dwi Anggraini; Usman Pagalay; Achmad Nashichuddin (Jurnal Riset Mahasiswa Matematika, 2022)
The brain tumor distribution model with immune cell response is in the form of a non-linear system of ordinary differential equations with five equations. Each equation describes how immune cells in the brain, namely macrophages ( ), CD8+ T cells ( ), TGF-  cytokines ( ) and IFN-  ( ) cytokines interact with tumor cells, namely glioma cells ( ). From the calculation of the equilibrium point, the tumor cell-free conditions (DFE) and the endemic conditions (END) were obtained, in which tumor cells in long-term conditions were always present in the patient's brain. By using certain parameter values, it can be illustrated that the END condition is locally asymptotically stable while the DFE condition is locally unstable. This indicates that brain tumor cells, namely glioma cells ( ) will increase to their maximum value of 882650 cells and remain at that number from day 1000 onwards.